Development of Performance Instruments to Assess Student Performance in Congregational Prayer Practices For Islamic Elementary School Grade II - Ernawati, Ernawati; Ridlo, Saiful; Elmubarak, Zaim (Journal of Research and Educational Research Evaluation, 2024)
This research is a research and development of performance assessment instruments for class II of Islamic Elementary School students in the practice of congregational prayer on fiqh subjects. The research was conducted at Al-Qolam Islamic Elementary School , Nurul Ilmi Islamic Elementary School, and Sambinae Islamic Elementary School in Bima City. Research method using the Mix method, where the research subject was Islamic Elementary School teacher that teach subject Fiqh at class II. The results showed that there were 3 instruments for assessing student performance in Congregational Prayer Practices, namely the p erformance instrument for the Priest which consisted of 23 statement items, the Main Congregation which consisted of 24 statement items and the Masbuk Congregation which consisted of 25 statement items. All instruments developed have been tested for validity, namely the performance instrument of Priest has an average V'aiken 0.87, the performance instrument of the Main Congregation is 0.85, and the performance instrument of the Masbuk Congregation is 0.86. While the reliability of the instruments analyzed using the inter-rater reliability (ICC) showed a reliable instrument with coefficient of reliability 0.79 for the performance instrument of Priests, 0.78 for the performance instrument of Main Congrthe egation, and 0.73 for the performance instrument of Masbuk Congregation.